Mathematical studies for the IB Diploma : standard and higher level - Genzer, Scott (New York : Oxford University Press, 2009)
A workbook for students studying for the International Baccalaureate Diploma Program in Mathematical Studies Standard Level that includes topic overviews, review questions, practice exams, answer explanations, and other teaching resources.
Young Adult
Keywords: Mathematics; Mathematics -- Examinations -- Study guides; Mathematics; Mathematics -- Examinations -- Study guides